2018
DOI: 10.1080/0305764x.2018.1518405
|View full text |Cite
|
Sign up to set email alerts
|

International doctoral students’ experience of supervision: a case study in a Chinese university

Abstract: is an Associate Professor in Beijing Language and Culture University (BLCU) and currently holds position of Vice-Dean of the School of Foreign Languages of Yili University in China. She graduated from Jilin University in China with MA degree in English Linguistics in 1994 and PhD in foreign language education and intercultural studies from Durham University in the UK in 2011. Her current research interest is in study abroad, Chinese language teachers teaching abroad, as well as the comparative study of teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Similarly, Bandura mentioned emotional status and self-efficacy (Bandura,1986(Bandura, , 1997, by the same token; our study noted that international students' psychological strengths in dealing with research related challenges at Chinese university where cheering, even if they have a lot to do and know to boost their research skill but they are motivated and persistent towards their goals and open-minded technique to overcome these challenges (Nazari et al, 2020), and for that, supervisor supportive has a significant role in promoting research creativity and innovation among international student (Fan et al 2018); the finding demonstrates following earlier studies that international supervisors are shown valuable and crucial for doctoral students research skill and knowledge development. (Wang and Byram, 2018;Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bandura mentioned emotional status and self-efficacy (Bandura,1986(Bandura, , 1997, by the same token; our study noted that international students' psychological strengths in dealing with research related challenges at Chinese university where cheering, even if they have a lot to do and know to boost their research skill but they are motivated and persistent towards their goals and open-minded technique to overcome these challenges (Nazari et al, 2020), and for that, supervisor supportive has a significant role in promoting research creativity and innovation among international student (Fan et al 2018); the finding demonstrates following earlier studies that international supervisors are shown valuable and crucial for doctoral students research skill and knowledge development. (Wang and Byram, 2018;Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A study regarding international doctoral researchers reported inadequate departmental support, insufficient focus on their research projects, and weak research collaboration with their supervisors (Larbi and Fu, 2017;Byram, 2018). Contrary to this, Chinese supervisors and international supervisees have shown that doctoral students find the existing system valuable and strong identification with the education system to get educational opportunities (Wang and Byram, 2018). That is due to the decent scholarship the Chinese government offer with less effort and competition.…”
Section: Research Contextmentioning
confidence: 97%
“…In foreign studies, the problem of scientific supervision has been considered in a large number of works (Chatterjee-Padmanabhan & Rossetto, 2017; Lee, 2018;Paré, 2017;Wang & Byram, 2019).…”
Section: The Influence Of Scientific Supervision Styles On the Professional Self-determination Of Graduate Studentsmentioning
confidence: 99%
“…2019 МЕЖДУНАРОДНЫЙ ОПЫТ ИНТЕГРАЦИИ ОБРАЗОВАНИЯ terms only. International experts recognize that foreign students positively influence the social and cultural diversity of the youth environment, bring new research ideas and experience to Master and PhD programs, and help strengthen international partnerships [12]. Benefits are numerous after their graduation too, as most students return home, but continue to maintain friendly, scientific and creative ties with their universities, becoming conductors of the soft power of the country where they received their education 4 .…”
Section: International Experience In the Integration Of Educationmentioning
confidence: 99%
“…Therefore, the educational migration from Kazakhstan to China shows continuous growth dynamics. Along with the availability of scholarships and China's economic boom 12 , Chinese education has become attractive for Kazakh youth for a number of other reasons.…”
Section: International Experience In the Integration Of Educationmentioning
confidence: 99%